Fighting Climate Change: The Role of Norms, Preferences, and Moral Values - Armin Falk; Peter Andre; Teodora Boneva; Felix Chopra (Center for Economic Studies and ifo Institute (CESifo), 2021)
We document individual willingness to fight climate change and its behavioral determinants in a large representative sample of US adults. Willingness to fight climate change – as measured through an incentivized donation decision – is highly heterogeneous across the population. Individual beliefs about social norms, economic preferences such as patience and altruism, as well as universal moral values positively predict climate preferences. Moreover, we document systematic misperceptions of prevalent social norms. Respondents vastly underestimate the prevalence of climate- friendly behaviors and norms among their fellow citizens. Providing respondents with correct information causally raises individual willingness to fight climate change as well as individual support for climate policies. The effects are strongest for individuals who are skeptical about the existence and threat of global warming.
Keywords: D64; D83; D91; Q51; Z13; 330